THEORETICAL STUDY OF THE MANOEUVRE PROCESS OF DESTROYED STONES AND FIBER IN THE NEW CONSTRUCTION SAW GIN WORKING CAMERA (Neo Scientific Peer Reviewed Journal, 2023)
A theoretical study of the process of movement of a dehydrated seed + fibrous medium in an saw gin working chamber has been carried out. The process representing the motion of a depleted seed + fibrous medium is mathematically constructed, on the basis of which the corresponding differential equations are constructed. The constructed differential equations were solved numerically in MAPLE-17 program, corresponding graphs were obtained and conclusions were given.